Internal Structure of the Beach Center Family Quality of Life Scale: Indonesian Version - Rahaju, Soerjantini; Lucas, Geraldyne Gavrielle Giovanna; Putri, Stefani Devina Arie (Universitas Ahmad Dahlan, 2024)
Family functioning has a broad impact on the psychological condition of family members, making it a variable often examined in research. The instruments used to measure family functioning vary in the dimensions they assess due to different theoretical approaches. One such measurement tool that comprehensively assesses dimensions and aligns with Indonesian Government Regulations is the Beach Center Family Quality of Life Scale (BCFQLS). However, its utilization in research in Indonesia remains limited. This study aimed to evaluate the psychometric quality of the BCFQLS using confirmatory factor analysis. The participants in this study were 331 married individuals who lived with their spouses and had at least one child. The results of the CFA indicate that the model fits the original structure of the BCFQLS, encompassing dimensions of family interaction, parenting, emotional well-being, and physical/material well-bein